ENHANCING NATIONAL RESILIENCE: STRATEGIC AND CRITICAL THINKING, AND THE WOGOS APPROACH IN MALAYSIA'S COVID-19 RESPONSE - Norshima Zainal Shah; Mohd Fouzi Sulaiman, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Strategic and critical thinking skills are important at times of crisis, and essential for fortifying and preserving national resilience, as they enable comprehensive analysis, proactive planning, and effective decision-making to safeguard a nation's interests, security, and long-term viability in an ever-evolving global landscape. This article addresses how Malaysia fought the COVID-19 outbreak with the Whole of Government, Whole of Society or WoGoS approach and, strategic and critical thinking skills. Using the recent COVID-19 pandemic as a case study, this article integrates coordination and collaboration frameworks to illustrate how the country utilised strategic and critical thinking skills in key decision-making processes during the crisis. It portrays the struggle of the country in the wake of the pandemic and gives testimony to the WoGoS approach. Malaysia's response revealed several notable findings, emphasising the significance of digitalisation, transparent communication, and preparedness for future similar events. Digitalisation and transparent communication are strongly linked to strategic and critical thinking, particularly in fostering coordination, collaboration, and innovation. By effectively incorporating strategic and critical thinking skills into both policymaking and contingency planning to address the challenge, and having public service agencies collaborate across different sectors, Malaysia was able to overcome the crisis and lay the foundation for long-term growth and development. It is evident that strategic and critical thinking skills are crucial in enhancing national power, but there is also the need to apply the WoGoS approach, not only during the crisis but in daily normal administration.